Social dialogue in the Public Services in South Asia: A comparative overview of the laws, institutions and practices in India, Nepal and Sri Lanka - Alistair Smith (International Labour Organization (ILO), 2022)
While revealing new challenges for public services, the Covid-19 pandemic has also cast renewed light on the state of social dialogue and labour relations practices in many countries. But the rationale for this study also has an earlier genesis: following an ILO Governing Body decision, a Global Dialogue forum was convened in 2014 to address the impact of the financial crisis and other challenges confronting labour relations in the public services. It identified the need for further research to "enable improved responses to situations of crisis and to address obstacles in the ratification of Conventions Nos 151 and 154". This report is mainly based on a qualitative desk top assessment of available secondary literature and primary legal texts to describe and contrast the state of freedom of association and the right to organize and collective bargaining in the public services in India, Sri Lanka and Nepal. Public service labour relations in these three south Asian countries are found to be in flux and prone to instability while operating with moderately effective to weak social dialogue mechanisms. Although freedom of association is constitutionally enshrined for public servants, it is restricted in law and practice. Trade Unions are well established but also highly fragmented and politicized.
Keywords: 330; social dialogue; public sector